SYSTEM DOCUMENTATION AS BASIS FOR COMPANY BUSINESS PROCESS IMPROVEMENT - Dewan Pelawi (CommIT (Communication and Information Technology) Journal, 2012)
Business process is an activity performed together to achieve business goals. Good business process will support the achievement of the organization’s plan to make profit for the company. In order to understand the business process, the business process needs to be documented and analyzed. The purpose of research is to make the system documentation as a basis to improve or complete the ongoing business process. The research method is system documentation. System documentation is a way to describe the operation of the system. System documentation consists of variety of forms depending on the needs of the system, which wish to be portrayed. The expected result is system documentation in the form of the proposed DFD and business process improvement. The obtained conclusions show that by doing system documentation will provide basic improvements to a better business process by analyzing the relationship between the process with another process, through the data, which are used together.Keywords: systems; documentation; system documentation; DFD